Perancangan alat permainan maze berbasis Lean UX untuk menstimulasi kognitif anak PAUD Kurikulum Merdeka - Kaffa Refiansya Junaedi; Ghia Tri Jayanti; Handayani Madania Insani; R. Moch. Rizal Hafiyan (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2026)
Cognitive development stimulation is very important in early childhood education because it affects thinking skills and learning readiness. At the age of 4–5 years, learning tools must be adapted to the way children learn. This study aims to create an educational maze game with User Experience (UX) guidelines to help the cognitive development of children aged 4–5 years in the context of the Merdeka Curriculum Early Childhood Education. The research used the Lean UX method, which included reading literature, observing how children learn, compiling design requirements, creating prototypes, and testing users. Based on the results of observations and evaluations, it was found that children responded positively to interactive and visually appealing media and that the application of UX principles in maze games increased children's engagement during learning, especially in their ability to focus, recognize patterns, and solve simple problems. In addition, the interaction between teachers and children also increased during learning activities. The novelty of this research is the application of the Lean UX approach as a framework for designing PAUD educational games that prioritize user experience in design decision-making. The findings of this study have implications for the development of learning media that is more participatory, contextual, and supports active learning in early childhood education